2019
DOI: 10.1101/603480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanopore sequencing and comparative genome analysis confirm lager-brewing yeasts originated from a single hybridization

Abstract: 22Background 23

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 101 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…The recent release of the first long-read sequencing assembly of S. pastorianus enabled a precise chromosomal mapping of the maltose metabolism genes (54) and showed that the Frohberg-type S. pastorianus strain CBS 1483 harbored one copy of SeAGT1 on the S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent release of the first long-read sequencing assembly of S. pastorianus enabled a precise chromosomal mapping of the maltose metabolism genes (54) and showed that the Frohberg-type S. pastorianus strain CBS 1483 harbored one copy of SeAGT1 on the S.…”
Section: Discussionmentioning
confidence: 99%
“…eubayanus ChrXV section (as in CDFM21L.1) of the chimeric chromosome formed from S. eubayanus ChrXV ( Se ChrXV) and Se ChrVIII (54).…”
Section: Discussionmentioning
confidence: 99%
“…This may have been facilitated by the occurrence of multiple copies of the SeAGT1 gene in the S. eubayanus ancestor, which could act as a sequence buffer to counteracting adverse effects of gene copy loss. The recent release of the first long-read sequencing assembly of S. pastorianus enabled a precise chromosomal mapping of the maltose-metabolism genes (Salazar et al 2019) and showed that the Frohberg type S. pastorianus strains CBS 1483 harbored one copy of SeAGT1 on the S. eubayanus CHRXV section (as in CDFM21L.1) of the chimeric chromosome formed from SeCHRXV and SeCHRVIII (Salazar et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A number of clades have become adapted to the production of fermented beverages or foods and these are regarded as prime examples of microbe domestication that quite often led to the existence of polyploid and/or aneuploid lineages (Strope et al 2015;Gallone et al 2016;Duan et al 2018;Peter et al 2018;Steensels et al 2019). The most widespread yeast-fermented product worldwide that uses another yeast "species" is lager beer, where fermentation is carried out by domesticated hybrids of S. cerevisiae and S. eubayanus (known as S. pastorianus and S. carlsbergensis) (Gallone et al 2019;Langdon et al 2019;Salazar et al 2019).…”
Section: Introductionmentioning
confidence: 99%